Chemoprevention of colon cancer: advantage of intermittent pulse treatment schedules quantified by computer simulation of human colon crypts. (10th August 2017) - Axelrod, David E; Bravo, Rafael
Abstract: Intermittent treatment schedules have been proposed to improve the tolerance of drugs for cancer chemoprevention. However, determining a maximum tolerated dose, and the extent of the improvement, has been challenging experimentally and clinically. In order to determine the quantitative advantage of intermittent pulse treatment schedules for the chemoprevention of colon cancer we have used a computer model of human colon crypts calibrated with measurements of human biopsy specimens. In simulations, crypts were treated with an agent that increases the probability that cells, both normal and mutant, would be removed at the top of the crypt. Sulindac, which increases apoptosis at the lumen surface, is such an agent. The effect of intermittent pulse drug treatment schedules were compared with constant drug treatment schedules. Crypts treated with intermittent pulse schedules have three times the maximum tolerated dose than crypts treated with constant schedules, and have a 10 year delay in the appearance of adenomas. Intermittent treatment schedules have previously been proposed for chemoprevention. Here computer simulations have quantified the effect on human colon crypts of intermittent treatment schedules and constant treatment schedules of a chemotherapeutic drug. Intermittent pulses have an advantage, they allow an increased maximum tolerated dose, and result in an increased chemoprevention by delay.